Fabrication and electrical characteristics of Perylene-3,4,9,10-tetracarboxylic dianhydride/p-GaAs diode structure - Soylu, Murat; Yakuphanoğlu, Fahrettin; Yahia, I. S. (Pergamon-Elsevier Science Ltd, 2012)
This study aims to experimentally investigate whether Perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) organic layer at p-GaAs/Ag interface affects electrical transport across this interface or not. The electronic properties of metal-organic semiconductor-inorganic semiconductor structure between p type GaAs and PTCDA organic film have been investigated via current-voltage (I-V) and capacitance-voltage (C-V) methods. The Ag/PTCDA/p-GaAs contact exhibits a rectification behavior with the barrier height of 0.74 eV and ideality factor value of 3.42. Modification of the potential barrier of Ag/p-GaAs diode was achieved by using thin interlayer of the PTCDA organic material. This was attributed to the fact that the PTCDA organic interlayer increased the effective barrier height by influencing the space charge region of GaAs. The low and high frequency capacitance-voltage plots were used to determine the interface state density of the diode. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Interface State Density; Organic Thin-Film; Barrier Height; Schottky Contacts; Fermi-Level; N-Type; Si; Transistors; Temperature; Voltage